2022
DOI: 10.1101/2022.10.18.509515
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A tissue injury repair pathway distinct but parallel to host pathogen defense

Abstract: Pathogen infection and tissue injury are universal insults that disrupt homeostasis. Innate immunity senses microbial infections and induces interferons (IFNs) to activate resistance mechanisms. Applying unbiased phylogenetic analysis, we show that interleukin-24 (IL24) is among the closest evolutionary homologs to the IFN family and shares a common ancestral origin. However, in contrast to IFNs, IL24 induction occurs specifically in barrier epithelial progenitors after injury and is independent of microbiome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 79 publications
(103 reference statements)
0
0
0
Order By: Relevance
“…As such, they are equipped with myriad receptors that detect bacterial products. There is growing appreciation for injury signals, beyond pathogen-and damage-associated molecular patterns (73), that are detected by keratinocytes and can induce reepithelialization (74). It is reasonable to hypothesize that an A. faecalis-derived peptide is sensed by keratinocyte receptors and induces a promigratory phenotype, although the identity of that signal will need to be identified in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…As such, they are equipped with myriad receptors that detect bacterial products. There is growing appreciation for injury signals, beyond pathogen-and damage-associated molecular patterns (73), that are detected by keratinocytes and can induce reepithelialization (74). It is reasonable to hypothesize that an A. faecalis-derived peptide is sensed by keratinocyte receptors and induces a promigratory phenotype, although the identity of that signal will need to be identified in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, targeting the AKR1C1 + inflammatory fibroblast might offer new therapeutic insights, especially in OV and UCEC. Intriguingly, WNT5A + inflammatory fibroblast has been shown to interact with diverse TME components configuring inflammatory and pro-tumorigenic milieu via WNT5A, GREM1, and IL24 41,[44][45][46] . Future studies that therapeutically target WNT5A + inflammatory fibroblasts should be pursued to mitigate deleterious consequences associated with these protumorigenic fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…S12E). Furthermore, WNT5A + inflammatory fibroblast showed strong interactions with fibroblast populations including desmoplastic fibroblasts (WNT5A:PTK7, WNT5A:ROR2, and GREM1:ACVR1), with themselves in homotypic interactions (WNT5A:PTK7 and GRE-M1:ACVR1), and BMP4 + fibroblasts (GREM1:ACVR1) to mimic wound repair process to potentiate mesenchymal proliferation and migratory phenotype of cells through both autocrine and paracrine mechanism 41,42 (Fig. 4D and Supplementary Fig.…”
Section: Deconvolution Of Tumor-normal Ecosystems Into Heterogeneous ...mentioning
confidence: 99%
See 1 more Smart Citation
“…1214 Human interleukin-24 (hIL-24) is notable for its wide range of biological actions, including its tumor-suppressing effects in various cancer forms. 1517 Although research has shown the ability of hIL-24 to inhibit tumor cell growth and promote apoptosis, its use in treating cervical cancer is not well explored. 1820…”
Section: Introductionmentioning
confidence: 99%